Development of novel solvent extraction method for determination of gold(III) using 4-heptylaminopyridine: Application to alloys and environmental analysis. Issue 3 (September 2016) - Khogare, Balaji T.; Kamble, Ganesh S.; Kokare, Arjun N.; Zanje, Sunil B.; Suryavanshi, Vishal J.; Anuse, Mansing A.; Piste, Pravina B.; Kokare, Balasaheb N.
Graphical abstract: Highlights: 4-heptylaminopyridine is a novel extractant for extraction and separation of gold(III) metal. Extraction of gold(III) has been carried out without any addition of synergent or modifier at room temperature. The developed conditions of separations have been successfully extended to recover gold(III) from binary and ternary metal ion mixtures, alloys and environmental samples. Abstract: In this paper, the solvent extraction of gold(III) from malonate media (0.04 mol L −1 ) has been studied by equilibrating aqueous phase having pH 2.5 with 10 mL of 0.07 mol L −1 4-heptylaminopyridine (4-HAP) as a novel anion exchanger diluted in xylene for 2 min. The extracted metal from organic phase was separated by stripping with 5.0 mol L −1 NH3 solution (2 × 10 mL). The effect of various parameters, such as pH, extractant concentration, weak acid concentration, equilibrium time, stripping agents, aqueous to organic volume ratio and diluents on the extraction of gold(III) was investigated. The extracted species has been evaluated from log D vs log C and species appears to be 1:2:1 (metal: acid: extractant). The selectivity of the method was checked by separating gold(III) from binary and ternary mixtures of associated metal ions as well as platinum group metals(PGMs). The separation of gold(III) from synthetic alloys and environmental samples was also carried out.